Czekałem na zimę. Wśród Polaków w Kazachstanie .......... 315 - Żaliński, Adam (Peregrynacje międzykulturowe: Księga jubileuszowa dedykowana prof. Tadeuszowi Palecznemu, 2025)
I WAS WAITING FOR WINTER. AMONG THE POLES IN KAZAKHSTANThis text is a record of part of a research trip to Kazakhstan, which took place in September and October 2024. The article contains elements of reportage, more or less elaborated material from field research in the form of interviews and observations, autoethnography and reflections on conducting field research, as well as account of the state of the Polish diaspora in this Central Asian country. I intentionally do not include here any excerpts from the statements of the Kazakh Poles who were informants for me. Instead, one can find utterances of other people I met.